2021
DOI: 10.3389/fnagi.2021.739948
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Cognitive-Motor Exergames in Geriatric Inpatient Rehabilitation: A Pilot Randomized Controlled Study

Abstract: Objective: The aim of this pilot randomized clinical trial was to test the feasibility and efficacy of an exergame-based cognitive-motor training program in geriatric inpatients.Methods: The study participants were randomly allocated to either the exergame intervention group or the control group. The control group received the standard rehabilitation treatment offered in the clinic. In addition to the standard rehabilitation program, the intervention group conducted supervised exergame training on 5 days per w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 88 publications
3
19
0
Order By: Relevance
“…The Dividat Senso is a stationary training platform with force sensors, linked to a screen ( Figure 2 ) that delivers fifteen exergames [described in previous studies ( 16 , 17 )]. It is already widely used in research ( 17 ) and clinical practice ( 16 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dividat Senso is a stationary training platform with force sensors, linked to a screen ( Figure 2 ) that delivers fifteen exergames [described in previous studies ( 16 , 17 )]. It is already widely used in research ( 17 ) and clinical practice ( 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…One training approach which efficiently lends itself to telerehabilitation in OA are so-called exergames, i.e., interactive digital games combining motor and cognitive exercises with video games targeting several physical and cognitive functions ( 14 ). Previous studies have shown that exergames lead to improvements in several physical functions such as lower extremity muscle strength ( 15 ), step reaction time ( 16 ), and balance ( 17 19 ) as well as in cognitive functions like short-term attentional span ( 20 ), processing speed ( 20 , 21 ), and executive functioning ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…NASA-TLX is used in a wide spectrum e.g. to assess surgeons' intraoperative cognitive workload 56 , to monitor the mental workload in geriatric inpatients during an exergame-based cognitive-motor training program 57 or to identify the association between several contextual match factors, technical performance, and external movement demands on the subjective task load of elite rugby league players 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is important to emphasize that these are only minor usability issues, and only minor refinements are required to optimize the exergame experience. This is also illustrated by recent studies showing that exergame-based training programs using the "Senso" are feasible; usable; and widely accepted in different populations including community-dwelling older adults [84], geriatric inpatients [51], and patients with major NCD [52], chronic stroke [85], or multiple sclerosis [86]. Therefore, when designing and developing an exergame-based training concept specifically for older adults with mNCD, these refinements should primarily target the adaptability and individualization of task demands and the optimization of the instruction of the exergames.…”
Section: Treatment Experience and Preferencesmentioning
confidence: 91%
“…This study is part of the first phase of the project, with the aim to specify a "set of design requirements that includes design considerations, accessibility recommendations, user modeling elements, and technological reflections to be followed in the design and development phase" [47,50], and it was combined with an extensive literature review and reflections on technology scoping and sustainability strategy (see steps 4 and 5 of phase 1 of our recently published methodological paper [47]). For the project, the exergame device "Senso (Flex)" (Dividat AG) was preselected on the basis of (1) our previous research, (2) because this device has already been shown to be feasible and well-accepted in geriatric patients [51] and patients with major neurocognitive disorder [52], and (3) because it is already widely used (and therefore available more widely and for longer term by end users and health care institutions) for motor-cognitive training within geriatric populations, physiotherapies, or rehabilitation clinics in Switzerland. On this basis, this qualitative study was designed to achieve the defined objectives in general; in addition, it also aimed to collect evidence about the previous experiences of experts or health care professionals with different exergame systems [including the "Senso (Flex)"].…”
Section: Overviewmentioning
confidence: 99%